Kinerja induk sapi peranakan ongole selama kebuntingan yang diberi ransum basal jerami padi dengan suplementasi daun lamtoro dan vitamin A - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Experiments were undertaken to evaluate performance of Ongole Crossbred cow during pregnancy that were fed rice straw basal diets supplemented with Leucaena (Leucochepala) leaf and vitamin A. Evaluation was done on gainweight, body score condition, and dysticia score of the cows, vigor score, and birthweight of calves. Forty Ongole crossbred cows were divided into 4 groups. The J+B group was fed rice straw and rice bran, the J+B+L group was fed rice straw, rice brand and Leucaena leaf meal, the J+B+VITA group was fed rice straw, rice bran, and vitamin A, and the J+B+L+VITA group was fed rice straw, rice brand, Leucaena, and vitamin A. The results of the experiment showed that there were significantly differences between the group on dry matter intake (P... Kata kunci: sapi peranakan Ongole, Kinerja induk Bunting, Jerami padi, Daun lamtoro, vitamin A.